Review of rain attenuation studies in tropical and equatorial regions in Malaysia: an overview - Ulaganathen, Kesavan; Abdul Rahman, Tharek; Abdul Rahim, Sharul Kamal; Islam, Md Rafiqul (IEEE, 2013)
Rain is a major source of attenuation for microwave propagation above 10 GHz. In tropical and equatorial regions, the rain intensity is high. Therefore, designing terrestrial and Earth-to-satellite microwave links is very critical and challenging. The raindrop-size distribution and the rain-rate distribution are two important parameters used for attenuation prediction. Both are proposed based on measured data and the rain-rate conversion technique. In this paper, rain attenuation was directly measured at different frequencies for terrestrial and Earth-to-satellite links, in order to investigate prediction models. The reduction factor and frequency scaling were investigated and proposed to predict total attenuation. Worst-month and annual statistics were also analyzed, based on measurements. Moreover, this paper summarizes all contributions related to rain-caused attenuation for microwave propagation in Malaysia’s tropical climate.